Designing social marketing activities to impact on shaping expectations of migrants health service encounters: The case of African Migrant blood donation in Australia. - Ferdous, A.; Polonsky, M.; Brijnath, Bianca; Renzaho, A. (2015)
Based on the findings of the nine focus group discussions with 88 participants from the African migrant and refugee community in Australia the chapter overall will examine how African migrants and refuges experiences in both home and host country shape their expectations of blood donation service encounters in Australia. The chapter then proposes a broader conceptual framework that highlights that cultural distance between home and host country also needs to be considered when implementing social marketing activities to shape health service expectations of migrants and refugees, with suggestions as to how this can be applied when targeting migrant consumers.